Low-level laser irradiation promotes proliferation of cryopreserved adipose-derived stem cells - Fernanda Ginani; Diego Moura Soares; Hugo Alexandre de Oliveira Rocha; Carlos Augusto Galvão Barboza (Einstein (São Paulo))
ABSTRACT Objective To evaluate the effect of low-level laser irradiation on proliferation and viability of murine adipose-derived stem cells previously submitted to cryopreservation. Methods Adipose-derived stem cells were isolated from inguinal fat pads of three mice, submitted to cryopreservation in fetal bovine serum with 10% dimethylsulfoxide for 30 days and then thawed and maintained in normal culture conditions. Culture cells were either irradiated or not (control) with an InGaAIP diode laser at zero and 48 hours, using two different energy densities (0.5 and 1.0J/cm2). Cell proliferation was evaluated by trypan blue exclusion method and MTT assay at intervals of zero, 24, 48, and 72 hours after the first laser application. Cell viability and apoptosis of previously cryopreserved cells submitted to laser therapy were evaluated by flow cytometry. Results The Irradiated Groups (0.5 and 1.0J/cm2) showed an increased cell proliferation (p<0.05) when compared to the Control Group, however no significant difference between the two energy densities was observed. Flow cytometry revealed a percentage of viable cells higher than 99% in all groups. Conclusion Low-level laser irradiation has stimulatory effects on the proliferation of adipose-derived stem cells previously submitted to cryopreservation.